DNA Damage Response and DNA Repair in Skeletal Myocytes From a Mouse Model of Spinal Muscular Atrophy. Issue 9 (September 2016) - Fayzullina, Saniya; Martin, Lee J.
Abstract : We studied DNA damage response (DDR) and DNA repair capacities of skeletal muscle cells from a mouse model of infantile spinal muscular atrophy (SMA) caused by loss-of-function mutation of survival of motor neuron ( Smn ). Primary myocyte cultures derived from skeletal muscle satellite cells of neonatal control and mutant SMN mice had similar myotube length, myonuclei, satellite cell marker Pax7 and differentiated myotube marker myosin, and acetylcholine receptor clustering. DNA damage was induced in differentiated skeletal myotubes by γ-irradiation, etoposide, and methyl methanesulfonate (MMS). Unexposed control and SMA myotubes had stable genome integrity. After γ-irradiation and etoposide, myotubes repaired most DNA damage equally. Control and mutant myotubes exposed to MMS exhibited equivalent DNA damage without repair. Control and SMA myotube nuclei contained DDR proteins phospho-p53 and phospho-H2AX foci that, with DNA damage, dispersed and then re-formed similarly after recovery. We conclude that mouse primary satellite cell-derived myotubes effectively respond to and repair DNA strand-breaks, while DNA alkylation repair is underrepresented. Morphological differentiation, genome stability, genome sensor, and DNA strand-break repair potential are preserved in mouse SMA myocytes; thus, reduced SMN does not interfere with myocyte differentiation, genome integrity, and DNA repair, and faulty DNA repair is unlikely pathogenic in SMA.